DEFECTS OF ETHNIC SOCIALIZATION OF MODERN YOUTH AND THEIR MANIFESTATIONS - Dagbaeva, S.B. (International Journal of Psychosocial Rehabilitation, 2020)
The paper deals with defects of ethnic socialization of young people. Exposure of youth to the influence of extremist, racist, and neo-fascist ideas is emphasized. The aim of our study is to identify the causes of addictive behavior in early adolescence, when addictive behavior itself is not yet formed, to find ways to prevent its occurrence. The main objective of the article is to analyze and substantiate the essence of addictive behavior as a consequence of feelings of loneliness of younger adolescents and destructive relationships with parents. The causes of these manifestations are the insufficient scope of certain stages of ethnic socialization of individuals, the experience of discrimination by race or ethnic origin, negative influence of certain radical and extremist subcultures of the youth, hater websites, certain mass media, etc., as a result of which a person becomes maladjusted and aggressive. The paper justifies the need to involve social institutions, such as family and school, in preventing ethnic socialization defects of the youth of today. This requires identifying age-related psychological features of ethnic socialization defects’ manifestations in connection with the formation of the value system, ethnic identity, and tolerance. It is emphasized that the obtained data can serve as the basis for developing the optimal ways to prevent and manage ethnic socialization defects of modern young people, which are due to the current social situation, as well as the needs and interests of the younger generation.